Synthesis and Properties of Lewis Acidic Perfluoroorganotin Halides with 2, 3, 5, 6‐Tetrafluoropyridyl and Pentafluoroethyl Substituents. Issue 40 (16th October 2017) - Wiesemann, Markus; Stammler, Hans‐Georg; Neumann, Beate; Hoge, Berthold
Abstract : In this paper, the synthesis of perfluoroorganotin bromides featuring 2, 3, 5, 6‐tetrafluoropyridyl (C5 F4 N) and pentafluoroethyl (C2 F5 ) substituents of the general composition BrSn(C2 F5 ) n (C5 F4 N)3– n ( n = 0–2) is discussed. The utilization of the p ‐tolyl unit as a protecting group and LiC5 F4 N and LiC2 F5 as perfluoroarylation and alkylation reagents allows a stepwise sequence of deprotection with HX (X = Cl, Br) and substitution to afford heteroleptic stannanes with three different substituents. In the solid state, BrSn(C5 F4 N)3 and BrSn(C2 F5 )(C5 F4 N)2 readily add water or acetonitrile and increase their coordination numbers. These results emphasize the Lewis acidic character of such perfluoroorganotin halides. Abstract : The utilization of p ‐tolyl protecting groups and LiC5 F4 N and LiC2 F5 as perfluoroarylation and alkylation reagents allows the formation of heteroleptic stannanes with three different substituents through stepwise deprotection with HX (X = Cl, Br) and substitution. The addition of water and acetonitrile to solid BrSn(C5 F4 N)3 and BrSn(C2 F5 )(C5 F4 N)2 emphasizes their Lewis acidic character.